Richard Ashcraft, Revolutionary Politics and Locke’s ’Two Treatises ses of Government; tenże, Locke’s ’Two Treatises of Government - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1989)
Recenzja: Richard Ashcraft, Revolutionary Politics and Locke’s ,Two Treatises of Government’, Princeton University Press: Princeton 1986, s. XXII + 613; tenże, Locke’s ,Two Treatises of Government’, Allen and Uniwinn: London 1987, s. XII + 316.